Educational Needs Assessment According to the Religious Commitment, Mental Health and Hope in Cancer Patients of Shahid Rajaee Hospital ,Babolsar - Hamid Shafie Arabi; Ramazan Hassanzadeh; Daruosh Ghasemian; Ali Shabestani Monfared (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVE: The purposes of this study were notification to the importance of mental health and hope in cancer patients with emphasis on need to religious and mental health promotion training courses. METHODS: This descriptive - analytic cross- sectional study was performed on 100 cancer patients of Shahid Rajaee Hospital in Babolsar. The three questionnaires for assessment of religious commitment, mental health and hope, based on Likert scoring method, were used .Data analysis was performed by SPSS software version of 17. FINDINGS: Mental health and hope status of radiation therapy patients were greater than chemotherapy patients. There are significant relationships between religious commitment, mental health, and hope. There are differences in mental health and hope status between male and female cancer patients. In this study female patients had worse status. CONCLUSION: According to the relationships between religious beliefs, mental health and also hope in these patients, it seems that they need to strengthen the religious beliefs as well as the improvement of mental health and hope and utilization of palliative care centers especially for women patients.